Sistem Konversi Data Excel Menjadi MySQL untuk Efisiensi Pengolahan Data pada PT. Afra Indo Safety - Anggie Syahputra; Farizi Ilham; Barren Al Faridzi; Thio Mandala Putra (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Microsoft Excel is still widely utilized by organizations for data management activities due to its user-friendly and flexible nature. Nevertheless, spreadsheet-based data storage faces several challenges, including duplicate records, input inaccuracies, inefficient information retrieval, and limitations in data integration. This study aims to develop a system capable of converting and integrating data from Excel files into a MySQL database in order to improve the effectiveness and accuracy of data management processes. The research methods include observation, interviews, literature review, and software development using the Waterfall approach, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The system was developed using PHP and MySQL and is equipped with features such as Excel file uploading, data mapping, data validation, and automated data migration into the database. The implementation results demonstrate that the system can accelerate data processing activities, minimize recording errors, maintain data consistency, and facilitate users in accessing and managing information in a more organized manner. Therefore, the developed system can serve as an effective solution for supporting more efficient, accurate, and integrated organizational data management.